BURDEN OF TUBERCULOSIS - COMBATING DRUG RESISTANCE - Javaid, Arshad (Journal of Postgraduate Medical Institute, 2011)
Tuberculosis (TB) is a medical, social and economic disaster of immense magnitude and is a major global health concern. It is currently the leading cause of death among curable infections. World Health Organization (WHO) data show that approximately one third of the world's population is infected with TB. Approximately 8 million people become infected annually, resulting in more than 2 million deaths each year1,2. The emergence of multidrug resistant tuberculosis (MDR-TB) has made the problem more pronounced, and its increasing incidence has turned it into a global threat.